Political Leadership in the Soviet Union
XI, 245 p.
Keywords: The central leadership of the Soviet political system in Moscow is analyzed by a group of Western political researchers. The text covers the entire Soviet period from 1917 to the present day, but special emphasis is placed on the post-Stalin years and new developments of the 1980s.